A study investigating how the albumin-globulin ratio relates to depression risk within U.S. adults: a cross-sectional analysis - Xu, Qi; Wang, Jiale; Li, Hanzhi; Chen, Xiaohui (Frontiers in Nutrition, 2024)
The relationship between the albumin-to-globulin ratio (AGR) and depression is not well understood. This analysis aims to investigate the relationship between AGR in conjunction with depression in U.S. adults.Methods: This study analyzed information from 31,363 individuals collected by NHANES during the years 2005 to 2018. The PHQ-9 scale was employed to gauge depression, where a score of 10 or above signified depression. Weighted multivariable logistic modeling along with smooth curve fitting were applied to explore the AGR-depression connection. To confirm our findings, we carried out sensitivity analyses, subgroup analyses, and interaction tests.After adjusting for confounding variables, a higher AGR is associated with a lower risk of depression (OR = 0.61, 95% CI: 0.47-0.79). Dividing AGR into quartiles revealed that participants in the highest quartile (Q4) of AGR had a markedly lower risk of depression than those in the lowest quartile (Q1) (OR = 0.64, 95% CI: 0.53-0.77). Using smooth curve fitting, we suggested a possible linear inverse association connecting AGR with depression. Further subgroup and sensitivity analyses supported these findings, although factors such as diabetes and hypertension might influence the relationship.Our findings indicate that elevated AGR levels correlate with a lower risk of depression. The findings suggest AGR as a potential biomarker for depression screening and prevention. Further studies are required to determine causality and clarify the mechanisms between AGR and depression.